2007
DOI: 10.1080/10255840701283988
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the tibio-femoral response to finite element modeling parameters

Abstract: A generic finite element (FE) model of the lower limb was used to study the knee response in-vivo during a one-legged hop. The approach uses an explicit FE code and a combination of estimated muscle forces and measured three-dimensional tibio-femoral kinematics and ground reaction force as input to the FE model. The sensitivity of the simulated tibio-femoral response to variations of key geometric and material parameters was investigated by performing a total of 38 different simulations. The amplitudes of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…The menisci were therefore modeled as linearly elastic, transversely isotropic materials [1,2,4,9,10,16,25,30,[34][35][36]39,[43][44][45]52], where the modulus and Poisson's ratio were 20 MPa and 0.2, respectively, in the radial and axial directions, and 140 MPa and 0.3, respectively, in the circumferential direction [4,30,45,52]. Time dependent effects of the cartilage and menisci properties were not considered due to the quasi-static nature of the models [4,7,8,23,30,32,35,[40][41][42]48,53,54]. The anterior and posterior meniscal roots for each meniscus were modeled as linear springs with spring constants of 2000 N/mm [9,23,25,30,35,36,45,52].…”
Section: Materials Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The menisci were therefore modeled as linearly elastic, transversely isotropic materials [1,2,4,9,10,16,25,30,[34][35][36]39,[43][44][45]52], where the modulus and Poisson's ratio were 20 MPa and 0.2, respectively, in the radial and axial directions, and 140 MPa and 0.3, respectively, in the circumferential direction [4,30,45,52]. Time dependent effects of the cartilage and menisci properties were not considered due to the quasi-static nature of the models [4,7,8,23,30,32,35,[40][41][42]48,53,54]. The anterior and posterior meniscal roots for each meniscus were modeled as linear springs with spring constants of 2000 N/mm [9,23,25,30,35,36,45,52].…”
Section: Materials Propertiesmentioning
confidence: 99%
“…It has been shown that under this condition, the biphasic response of cartilage can be negligible and the single-phase linear isotropic constitutive law be applicable [40,41]. Therefore, cartilage was modeled as a homogeneous, elastic, linearly isotropic material [1,2,[4][5][6][7]9,16,23,25,30,32,33,[35][36][37][38][39][42][43][44][45][46] with a modulus of 15 MPa [4,9,25,30,35,45] and a Poisson's ratio of 0.46 [31][32][33]47,48].…”
Section: Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…see references [61] to [63]). Other experimental [64][65][66] and computational [62] studies have shown that varying ligament attachment site locations by as little as 2 mm affected joint kinematics. Due to the expensive computational cost of exploring all combinations and levels of input parameter variations, constraint sensitivity predictions typically involved discrete changes in ligament input parameters (stiffness) and were focused on the cruciate ligaments under specific loading scenarios.…”
Section: Joint Mechanicsmentioning
confidence: 99%